Prevalence of USA300 Colonization or Infection and Associated Variables During an Outbreak of Community-Associated Methicillin-Resistant Staphylococcus aureus in a Marginalized Urban Population - Mark Gilbert; Judy MacDonald; Marie Louie; Dan Gregson; Kunyan Zhang; Sameer Elsayed; Kevin Laupland; Diane Nielsen; Virginia Wheeler; Tara Lye; John Conly (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: In 2004, an outbreak of the USA300 strain of methicillin-resistant Staphylococcus aureus (MRSA) was identified in persons with histories of homelessness, illicit drug use or incarceration in the Calgary Health Region (Calgary, Alberta). A prevalence study was conducted to test the hypotheses for factors associated with USA300 colonization or infection.